Systematization of the program for creating university-based associative companies and sustainable development goals: Case: Costa Rica - Li Bonilla, Federico; Espinach Rueda, Monserrat (Cooperativismo & Desarrollo, 2024)
The systematization of the program for the creation of university-based associative enterprises of the community for the territory is presented, from the proposal of the Social Spin Off model, whose purpose is to generate social progress, which is applied from the Universidad Estatal a Distancia de Costa Rica, which is based on knowledge transfers, This model is based on knowledge transfers and free academic support to communities with the lowest indicators of the Social Progress Index, which is supported by cooperative entrepreneurship, with the overall objective of “promoting low-tech business ideas”, but which will help to start having a life with greater purchasing power through decent work. The methodology used in the last four years has been action-research, thus creating cooperatives and guiding them until they reach their economic equilibrium point, and generating territorial development, inclusive and quality education to the participants, contributing to close the digital gap, accompanying them in their maturation. The approach to the state of the art was carried out through literature review and expert knowledge. The inquiry is qualitative, descriptive, and cross-sectional. The analysis of the State Policies of Costa Rica, as well as the implementation of the sustainable development goals (SDG) and their relationship with the social economy, under the foundations of cooperativism; as well as the understanding of the Costa Rican cooperative model. The monitoring of indicators of the Social Progress Index (IPS) that measure compliance with the 2030 Agenda as instruments of territorial development scope is detailed. The social spin off model allows generating knowledge transfer to promote territorial development in the most vulnerable territories of the country. Currently the model has four years of operation, started in October 2019, has more than 600 people involved in 16 pre cooperative groups, and 12 cooperatives formed.
Keywords: Cooperativism; Social Planned Spin-Off Model; Sustainable Development Goals